Development of Embedded System for Centralized Insomnia System - Novi Azman; Mohd Khanapi Abd Ghani; Muhammad Haikal Satria; Muhammad Zillullah Mukaram (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Insomnia is a common health problem in medical field as well as in psychiatry. The measurement of those factors could be collected by using polysomnography as one of the current standards. However, due to the routine of clinical assessment, the polysomnography is impractical and limited to be used in certain place. The rapid progress of electronic sensors to support IoT in health telemonitoring should provide the real time diagnosis of patient at home too. In this research, the development of centralized insomnia system for recording and analysis of patient with chronic-insomnia data is proposed. The system is composed from multi body sensors that connected to main IOT server. The test has been done for 5 patients and the result has been successfully retrieved in real time.